Determinan Perilaku Pembelian Produk Halal pada Ritel Lokal: Studi Empiris di Toserba Sunan Drajat Cabang Nguwok - Tito Nur Mustika; Nur Hayya Hikmah Falabibah; Anas Alhifni (JOM, 2026)
The rapid development of the halal industry in Indonesia has led to an increasing number of halal-labeled products in the local retail market. This study aims to identify the consumer preference factors that influence purchasing behavior of halal products at Toserba Sunan Drajat, Nguwok Branch, Lamongan. The study focuses on three factors: trust in halal products, price, and product quality. This research employs a quantitative method with an associative and explanatory approach. Data were collected through questionnaires distributed to 50 respondents using an accidental sampling technique. The results show that the three preference factors simultaneously have a significant effect on halal product purchasing behavior. Partially, price is the dominant and significant predictor. Meanwhile, trust and product quality, although not individually significant, still have a positive influence within the model. These findings imply that competitive pricing is a key factor in managing halal products in pesantren-based local retail. Furthermore, this study provides empirical contributions to the study of halal consumer behavior in the context of local retail, which remains relatively underexplored in Indonesia.